Pelatihan Peningkatan Kompetensi Pedagogik Guru Bahasa Inggris Pebelajar Muda di Kampung English Desa Temulus Kabupaten Kudus - Nadiah Ma'mun (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
Teaching English to young learners has been a concern of language teaching experts over the last decade in non-English speaking countries. Teaching English in this context should have a positive impact on young learners' English mastery according to the child's age development if teaching simple vocabulary and grammar are taught using songs and games. The use of these two media according to Chou's (2012) research has a positive impact because songs can make it easier for children to memorize vocabulary, while the use of games can increase positive attitudes to participate in learning. Therefore, teaching English with this media is trained for English teachers in Kampung English, Temulus Village, Kudus Regency with the aim of making English learning more fun, interesting, and motivating for students.